Karakteristik Komunikasi Politik dalam Pidato Presiden Prabowo Subianto Pelantikan Presiden Republik Indonesia Periode 2024-2029 - Kapege, Laode Aharuddin; ., Munawir (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
The inaugural speech of President Prabowo Subianto on October 20, 2024, represents a strategic form of political communication aimed at conveying the direction of government policies at the beginning of his administration. This study aims to analyze the characteristics and functions of political communication within the speech. The research employs a descriptive qualitative method using content analysis of President Prabowo Subianto’s inaugural address. The results indicate that the characteristics of political communication in the speech reflect a one-way communication model combined with a strong rhetorical style, emphasizing national unity, economic development, and the strengthening of national defense and security. President Prabowo acts as an elite political communicator who functions as both a policymaker and a public opinion leader. Functionally, the speech serves to inform the public, justify and support governmental policies, build political legitimacy, and initiate dialogue between the government and citizens. Moreover, in the context of international relations, the speech helps construct Indonesia’s political image as a decisive, inclusive, and progressive nation.